Occurrence of the genus Actus (Mononchida: Mylonchulidae) in Vietnam - Thanh Tam, Vu Thi (Academia Journal of Biology, 2017)
Two species of Actus, A. conoidus and A. salvadoricus, are recorded, described and illustrated for the first time from Vietnam. Actus conoidus was collected from Bach Long Vi Island, Quang Ninh Province; its measurements and features corresponded well with the type population from Manipur, India. Actus salvadoricus was found in the Na Hang preservation area, Tuyen Quang Province; its measurements and morphological features corresponded well with the type population from Ilopango, San Andres, Sonsonate and El Recreo, El Salvador, as well as those from Okinawa, Japan.   Citation: Vu Thi Thanh Tam, 2017. Occurrence of the genus Actus (Mononchida: Mylonchulidae) in Vietnam. Tap chi Sinh hoc, 39(3): 264-269. DOI: 10.15625/0866-7160/v39n3.9269. *Corresponding author: vtam7572@yahoo.com Received 2 March 2017, accepted 20 August 2017